2005
DOI: 10.1021/je0400052
|View full text |Cite
|
Sign up to set email alerts
|

Viscosity, Density, and Refractive Index of Some (Ester + Hydrocarbon) Binary Mixtures at 303.15 K and 313.15 K

Abstract: The viscosity, density, and refractive index of binary mixtures of ethyl formate or ethyl benzoate with o-xylene, m-xylene, p-xylene, and ethylbenzene were determined at 303.15 K and 313.15 K and atmospheric pressure for the whole composition range. From the experimental measurements, the deviations in viscosity, Δη, were correlated accurately with the Redlich−Kister polynomial equation. The deviations in molar refraction, ΔR, were calculated from the Lorentz−Lorentz equation. The experimental viscosities were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Studies reported the ΔR of binary mixtures based on volume fraction 14,15,31,[46][47][48]62,68,69 and mole fraction basis. 9,52,65,70 It is implied that there is no general rule that states how to interpret molar refractivity function. 68,69 In addition, as reported by Konti et al, the deviation in molar refractivity with volume fraction is based on the Lorentz−Lorentz mixing rules.…”
Section: Resultsmentioning
confidence: 99%
“…Studies reported the ΔR of binary mixtures based on volume fraction 14,15,31,[46][47][48]62,68,69 and mole fraction basis. 9,52,65,70 It is implied that there is no general rule that states how to interpret molar refractivity function. 68,69 In addition, as reported by Konti et al, the deviation in molar refractivity with volume fraction is based on the Lorentz−Lorentz mixing rules.…”
Section: Resultsmentioning
confidence: 99%
“…The negative values viscosity deviation indicates that the dispersion forces are dominant. [16][17][18] The viscosity deviation (∆ŋ) values indicate that there is a survival of dispersion and dipolar forces between dissimilar molecules and associated with the variation in shape and size of the dissimilar molecules. The obtained values suggest that the existence of intermolecular force upon mixing of three binary liquid mixtures.…”
Section: Resultsmentioning
confidence: 99%
“…Vogel and Weiss 23 clarified that mixtures with solid communications between various molecules and negative deviations from Raoult's law display positive viscosity deviations while for mixtures with positive deviations of Raoult's law and without particular connections, the viscosity deviations are negative. 24 , which recommends that the position of -CH 3 groups on the aromatic ring assumes a generous part in choosing the extent ∆η and thus, the order of collaboration between the component molecules of the mixtures. The stereo normality of methyl groups in o-xylene is such that the steric repulsion is more.…”
Section: Viscosity Deviationmentioning
confidence: 99%